How, What, and Where You Sample Environmental DNA Affects Diversity Estimates and Species Detection - Anish Kirtane; Leif Howard; Caitlin E. Beaver; Margaret E. Hunter; Gordon Luikart; Kristy Deiner (Environmental DNA)
ABSTRACT Environmental DNA (eDNA) is a complex mixture of DNA, varying in particle sizes and distributed heterogeneously in aquatic systems. Optimizing eDNA sampling is crucial for maximizing species detection, particularly in high‐risk scenarios like invasive species management. In this study, we compare two eDNA sampling methods ‐ namely tow net and grab sample, where the tow nets process large volumes of water (3500–7000 L) through a 64 μm pore size and the grab samples process 1 L sample at a single point through 0.45–1.2 μm pore size membranes. We compared these methods to ascertain what most influences (1) the detection of invasive species (Dreissena mussels and Burmese pythons) using qPCR or ddPCR and (2) total diversity monitoring of metazoan, protist, and fungi community using a COI marker and plant communities using the ITS marker. Sampling was conducted across a wide geography and diverse aquatic environments in Minnesota and Florida, USA, and Switzerland. The tow net samples had significantly higher eDNA yield compared to grab samples; however, they exhibited equal or lower alpha diversity of OTUs (Operational Taxonomic Units). The two sampling methods measured different beta diversity of communities detected with the COI marker across all three regions, highlighting the impact of the sampling method on the diversity of eDNA captured. In comparison, the beta diversity of plant eDNA was less impacted by the sampling method. We found no clear difference in detection for the invasive species targets based on the eDNA sampling method. These results underscore the need for pilot studies before conducting biodiversity inventory and monitoring, and a need for a greater understanding of not just how much, but also what, eDNA is captured depending on method choice, considering both spatial and particle size heterogeneity.